Pierre Keller, Le Kilo-Art - Dirié, Clément 1981- (JRP Ringier, 2018)
This publication revives the fascinating adventure of Pierre Keller's invention and dissemination of the 'Kilo-Art, ' the 'Swiss standard for art measurement.' For the two years 1972 and 1973, the young artist - now a key figure of the contemporary artistic and pedagogical scene in Switzerland - dedicated his life to what he called 'conceptual art with realization.' From its first production tests to its exhibition in Geneva, Lausanne, and Venice, through the voluminous correspondence needed for its ratification by the Swiss Federal Office for Weights and Standards, this book follows every step of the birth of the 'Kilo-Art.' To be interested today in the 'Kilo-Art' is to understand how a young Swiss artist, informed by the lessons of Marcel Duchamp and American Conceptual art, could, at the beginning of the 1970s, propose an artwork more subversive that it may initially appear, in which avant-garde art meets the normative administrative system
Impressum: Cet ouvrage accompagne l'exposition de Pierre Keller à l'espace Palais, Neuchâtel, présentée du 18 mai au 17 juin 2018
Keywords: Keller, Pierre -- 1945-2019; Keller, Pierre / 1945- / Exhibitions; Conceptual art / Switzerland / Exhibitions; Keller, Pierre / 1945-; Conceptual art; Switzerland; Exhibition catalogs; Ausstellungskatalog -- Palais Galerie -- 18.05.2018-17.06.2018 -- Neuenburg, Schweiz